Liquidity, Asset Returns and Firm Value: Evidence from the UK Market - Khan, Saud Waheed (2012)
Liquidity risk has an utmost importance for investors and it serves as an essential theme in finance. Liquidity’s importance cannot be underestimated or belittled in asset pricing. This study takes an initiative to reveal liquidity and stock returns association in the UK market. The study consists of sample of 451 companies on London Stock Exchange. Two methodologies, portfolio and panel-data approach have been implemented to achieve research objectives. We find that liquidity risk is priced on London Stock Exchange but asset pricing models fail to explain returns to a large extent. CAPM does not capture liquidity risk and Liquidity Augmented Model explains returns better than Fama-French Three Factor Model. Amihud illiquidity and relative spread are found to be better measures of liquidity. The panel-data estimations also support liquidity risk hypothesis. This paper concludes that illiquid stocks require higher risk premium. Abating market influence and utilizing asset specific liquidity in regression shows that it is also a priced factor. The tests depict that illiquid stocks have higher illiquidity or liquidity volatility. The unexpected illiquidity is statistically insignificant. During the financial crisis, the innovations in market illiquidity keep more importance than asset specific illiquidity and other characteristics. Finally, profitability is found to be positively related to liquidity.